ESSENCE, FUNCTIONS, THEORETICAL AND METHODOLOGICAL PROBLEMS OF MODERN LOCAL LORE - Kashaba , O.; Shcherbyna , I. (Problems of Engineer-Pedagogical Education, 2023)
The system of modern humanitarian education should focus on the formation of a person who is able to translate cultural values, norms, ideals, and forms of reproduction of the national-cultural world, to promote the formation of interethnic tolerant relations. Local lore as a component of humanitarian education contributes to the activation of the creative potential of students, reveals their diverse opportunities, creates conditions for personal and public interests, and cultivates civic competencies. The authors of the article made an attempt to summarize the existing experience of domestic local lore studies, to analyze the main directions of research and methods of their study, as well as to reveal theoretical questions about the subject, object and tasks of local lore. The article analyzes the functions and essence of local lore in the modern period of development of Ukrainian society and describes the main directions of local lore research. Emphasis is placed on the educational and consolidating function of local lore in the process of unification of the Ukrainian nation as a result of military aggression from the Russian Federation. Local lore research is transformed from a methodological approach into a general pedagogical principle and creates a basis for the formation of deep professional knowledge and historical thinking, contributing to the creative understanding of the experience gained by local historians from different regions of Ukraine. The use of local lore material in the teaching of humanities and the practical application of acquired knowledge about the native land provide ample opportunities to increase the interest of students in the cultural and historical heritage of the Ukrainian people, to activate creative potential, worldview and national dignity of the youth.